2023
DOI: 10.1210/clinem/dgad406
|View full text |Cite
|
Sign up to set email alerts
|

Does Elevated High-Density Lipoprotein Cholesterol Protect Against Cardiovascular Disease?

Abstract: High-density lipoprotein (HDL) contributes to reverse cholesterol transport, which is one of the main explanations for the described inverse association between HDL-cholesterol (HDL-C) and atherosclerotic cardiovascular disease (ASCVD) risk. However, efforts to therapeutically raise HDL-C levels with niacin, fibrates, or cholesteryl ester transfer protein inhibitors have not demonstrated a reduction in ASCVD events when compared to placebo among individuals treated with statins. Furthermore, mendelian randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Interestingly, evidence suggests that along with the anti‐inflammatory, antioxidant and antithrombotic properties, HDL‐C is involved in the immune responses by the modulation of lipid raft components in immune cells [ 40 ]. Moreover, it has been reported that chronic inflammation can change the anti‐inflammatory function of HDL‐C to pro‐inflammatory function [ 11 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, evidence suggests that along with the anti‐inflammatory, antioxidant and antithrombotic properties, HDL‐C is involved in the immune responses by the modulation of lipid raft components in immune cells [ 40 ]. Moreover, it has been reported that chronic inflammation can change the anti‐inflammatory function of HDL‐C to pro‐inflammatory function [ 11 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, HDL‐C as a component of MetS is a cardioprotective marker with contribution in the reverse cholesterol transport pathway and anti‐inflammatory, antioxidant and antithrombotic properties [ 9 , 10 ]. However, in addition to the HDL‐C concentration, its function is also one of the factors influencing its anti‐inflammatory properties [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classically, it is known that HDL-C is inversely associated with CVD risk ( 11 ). However, some studies report that very high levels of HDL-C may increase CVD risk and mortality ( 57 , 58 ). Further clarification is needed in future studies.…”
Section: Discussionmentioning
confidence: 99%